Criminal compliance como mecanismo de proteção contra a criminalidade econômica - Felicio, Guilherme Lopes (2018)
This work aims at analyzing criminal compliance, a political-criminal instrument based on a prevention, willing to optimize in the corporate scope the implementation of an efficient organization system that removes the practice of delinquent conduct, demonstrating that this mechanism can assist the Law Criminal law in confronting economic crime and in its task of effectively protecting legal assets of a supra-individual nature. The effects of globalization and constant social developments have led to the formation of a new layer of crime, which not only causes more extensive damage and difficult reparation, but which affects society as a whole, the economic order and goes beyond the borders of the national territory, of legal persons for the commission of offenses or, at least, of their structure. In this way, it is fundamental that the Criminal Law conforms to the contemporary reality. Thus, aiming at effective protection of supraindividual legal assets, above all, the economic order, the adoption of a preventive stance by the Criminal Law is highlighted. In this scenario, it is hosted in the business of compliance, an administrative management structure introduced in the corporate governance scheme used by companies in their internal scopes that observes the state norms and operates in order to prevent the diversion of conduits that may eventually fall in their legal accountability. This way of working compliance, based on prevention, awakens the interest of Criminal Law that can perfectly use this instrument to protect its legal assets against economic crime. It should be noted that Brazilian legislation recommends that companies implement a compliance management system, however they address the issue in a non-committal manner, and also proposes in this work that Brazil prosecute the legal entity in order to highlight the effectiveness of compliance if related to a model of criminal liability of the legal entity. For the development of the work, through a deductive method under bibliographic references, we study the criminal protection of legal assets in the light of the Federal Constitution of 1988, economic crime, criminal compliance and criminal liability of the legal entity, demonstrating the relevance of the issues and between them, in search of safe answers to the problems that emerge on the subjec